Cleavage of adenosine 5'-monophosphate during uptake by Streptomyces griseus. - Martin, J F (1977)
Unlabeled adenine brought about a (delayed) decrease in radioactivity that had been taken up by phosphate-limited resting cells of Streptomyces griseus from [14C]adenine-labeled adenosine 5'-monophosphate (AMP). Inorganic phosphate, on the other hand, stimulated adenine uptake from AMP, presumably by activating an energy-dependent active transport mechanism. Unlabeled phosphate rapidly diluted the uptake of radioactivity from [32P]AMP. Adenine inhibited uptake of [32P]AMP but not that of [32P]orthophosphate; adenine is thought to act by inhibiting the cleavage of AMP. The uptake of 32P and 14C from double-labeled AMP showed marked differences; 32P was taken up much faster into both cells and nucleic acids. These data indicate that uptake of AMP components takes place after extracellular dephosphorylation of the nucleotide.